Machine tool, flexible manufacturing systems and automatization of procedures projection - Gatalo, Ratko; Rekecki, Jožef; Hodolič, Janko; Borojev, Ljubomir; Zeljković, Milan; Zeljković, Željko (Journal of Production Engineering, 1992)
At first, in the papers, it's pointed out that significant progress was made in the means of work in the previous period. This had a crucial influence on the development of teaching and scientific disciplines, which are cherished in the scope of the Laboratory for Machine Tools at the Faculty of Technical Sciences. Afterwards, the versatile analysis of results from the former development is done. This is carried out through achievements in the education process, scientific and research work, and material and personnel assumptions. The reason for that is a comparison with achievements in the teaching work at other faculties in the country and abroad. The aim of this comparison is to suggest new subject matters within the scope of the scientific discipline. The analysis of accomplishments in the teaching process particularly discusses studies for mechanical engineers and graduate studies. Results of scientific and research work are presented through a comparison of the number of realized scientific and research projects, themes, and the number and nature of published papers at the Institute for Production Engineering, the Department for Metal Chip Removal Machining, and the Laboratory for Machine Tools. Furthermore, in the pointed out accomplishments in the material base, particularly in the last development phase, when major scientific and research equipment is purchased. In the final part of the paper, the program's contents of particular subjects are compared with some faculties in the country. The scope of the curriculum at the Faculty of Technical Sciences and some faculties from abroad is also compared. At the end of the paper, it is concluded that in the Machine Tools, FMS, APP areas, and other disciplines in which the Department for Metal Chip Removal Machining is involved, the Faculty of Technical Sciences is becoming one of the leading faculties in the country.